2021
DOI: 10.3389/fsufs.2021.608868
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Agroforestry and the Food and Nutrition Security of Small Farmers of South-Western Ethiopia

Abstract: Agroforestry generally contributes to rural food and nutrition security (FNS). However, specialization on commodity-oriented agroforestry practices or management strategies can weaken local food sourcing when terms of trade fluctuate, as is the case of coffee in Ethiopia. Hence, this study assessed the trade-offs that smallholder farming households in south-western Ethiopia face between growing coffee in agroforestry systems and their food and nutrition security based on home production as well as markets. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…A study conducted in southwestern Ethiopia by [17] indicated that traditional shade coffee management practices can maintain a diverse suite of forest birds. In addition to the ecosystem benefits, agroforestry can contribute to food security [18] and income and a wide range of other products such as fuelwood, construction material, fodder, spices, and medicinal plants [19]. It is seen as a multidimensional system with biophysical and socioeconomic components.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in southwestern Ethiopia by [17] indicated that traditional shade coffee management practices can maintain a diverse suite of forest birds. In addition to the ecosystem benefits, agroforestry can contribute to food security [18] and income and a wide range of other products such as fuelwood, construction material, fodder, spices, and medicinal plants [19]. It is seen as a multidimensional system with biophysical and socioeconomic components.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of studies spanning 26 years across Latin America, Jezeer et al (2017) reported that lower costs and supplementary income from shade tree products made shaded systems more profitable than non-shaded systems. Products from shade trees, such as fruits, firewood, timber and other materials, can make up a substantial part of the total income from coffee AFS (Rice, 2008;Souza et al, 2010;Thuy et al, 2019), and highly diverse coffee AFS increase the household's food and nutrition sources, especially in the shortage season (Jemal et al, 2021). Payment for ecosystem services can also generate additional source of revenues for AFS-coffee farmers (Cole, 2010;Thuy et al, 2021).…”
Section: Coffee Farmers' Use and Perception Of Shade Treesmentioning
confidence: 99%
“…Food sovereignty has been qualified as the fifth pillar of food security, beyond supply, access, utilization and stability (Jemal et al 2018) and is linked to identity. Nutrition can be derived from forests, landscapes, homegardens and markets (Vinceti et al 2013;Ickowitz et al 2014;Powell et al 2015;Vira et al 2015;Fungo et al 2016;Jemal et al 2021). Storable staple foods, such as rice in Asia, can be more easily "outsourced" in exchange for marketable forest and agroforestry products than other complements of healthy diets (van Noordwijk et al 2014a).…”
Section: Identity Local Institutions Gendermentioning
confidence: 99%